Lersivirine, a Nonnucleoside Reverse Transcriptase Inhibitor with Activity against Drug-Resistant Human Immunodeficiency Virus Type 1 - Corbau, Romuald (American Society for Microbiology (ASM), 2010)
The nonnucleoside reverse transcriptase inhibitors (NNRTIs) are key components of highly active antiretroviral therapy (HAART) for the treatment of human immunodeficiency virus type 1 (HIV-1). A major problem with the first approved NNRTIs was the emergence of mutations in the HIV-1 reverse transcriptase (RT), in particular K103N and Y181C, which led to resistance to the entire class. We adopted an iterative strategy to synthesize and test small molecule inhibitors from a chemical series of pyrazoles against wild-type (wt) RT and the most prevalent NNRTI-resistant mutants. The emerging candidate, lersivirine (UK-453,061), binds the RT enzyme in a novel way (resulting in a unique resistance profile), inhibits over 60% of viruses bearing key RT mutations, with 50% effective concentrations (EC(50)s) within 10-fold of those for wt viruses, and has excellent selectivity against a range of human targets. Altogether lersivirine is a highly potent and selective NNRTI, with excellent efficacy against NNRTI-resistant viruses.